Mortality from epilepsy and status epilepticus in Brazil: analysis of the epidemiological profile (Research, Society and Development, 2022)
The objective of this article was to carry out an epidemiological analysis of the mortality profile from epilepsy and status epilepticus in Brazil. Methods: Retrospective transversal epidemiological study, with a quantitative and descriptive approach using data obtained from the Mortality Information System (MIS), according to sex and age group, between 2010 and 2019. Results: A total of 25,393 deaths were identified in Brazil, 89.8% of which were due to epilepsy (MPE) and 10.2% due to status epilepticus (EME). Of the total, 64.3% were male and 35.7% were female. The majority of cases were between 40 and 49 years. The North and Northeast regions presented the highest percentage of MPE and EME. In relation to the general mortality rates, an increase of 46.9% (MPE) and 68.4% (EME) was identified, with an increase in all geographic regions. The population mortality rate from epilepsy followed an upward trend with no statistically significant fluctuations. The mortality rate due to EME showed an increase between the general population and the male population, with an indication of a decrease among the female population. Conclusions: Contrary to the global parameter, Brazil showed an increase in the mortality rate from epilepsy, which may be related to the improvement in diagnosis, in the adequate recording of the underlying cause of death and in MIS in the last Years.